Correlation of concentration of fumonisins and yield grain of wheat - Protić Nada M.; Protić Rade J. (Zbornik Matice Srpske za Prirodne Nauke, 2005)
Wheat from different locations was served for the isolation of Fusarium spp. Isolates were precisely identified and multiplied for artificial inoculation. Three sorts of winter wheat were chosen: PKB Lepoklasa Jugoslavija and Francuska. To these sorts three different treatments were applied: artificial inoculation with the isolates of Fusarium spp. protection of wheat with fungicide Impact-C and follow-up of a spontaneous infection in different phenophasis of wheat development. The control was done with the same sort, of the same location, not covered by an experiment. The research lasted for three years. Phytopathological evaluation was done twice during vegetation. The sort of Jugoslavija had an average of 85% of infected plants, Francuska 65%, but PKB Lepoklasa during each of three years had 100% of infection by Fusarium spp. fungi. Presence of fungi Fusarium spp. causes production of numerous mycotoxins and we determined presence of fumonisins. The mentioned mycotoxin was found only in the treatment of artificial inoculation for each sort. Presence of fumonisins was proved by fluorometric method and concentration was by sorts as follows: Jugoslavija 0.30 mg/kg, Francuska 0.62 mg/kg, and PKB Lepoklasa 0.56mg/kg. In grains 100% infected by fungus, the concentration of mentioned toxins is of a greater quantity.